Flexible procurement systems is key to supply chain sustainability - Surajit Bag (Journal of Transport and Supply Chain Management, 2016)
Background: In this dynamic business environment, manufacturers are focusing primarily on delivery performance and competitive pricing to win orders. It is essential that manufacturers adopt flexible procurement systems (FPSs) in such an uncertain environment for business sustainability.